Hypothermia for encephalopathy in low and middle-income countries (HELIX): study protocol for a randomised controlled trial. - Thayyil,S; Oliveira,V; Lally,PJ; Swamy,R; Bassett,P; Chandrasekaran,M; Mondkar,J; Mangalabharathi,S; Benkappa,N; Seeralar,A; Shahidullah,M; Montaldo,P; et al. (Trials, 2017)
BACKGROUND: Therapeutic hypothermia reduces death and disability after moderate or severe neonatal encephalopathy in high-income countries and is used as standard therapy in these settings. However, the safety and efficacy of cooling therapy in low- and middle-income countries (LMICs), where 99% of the disease burden occurs, remains unclear. We will examine whether whole body cooling reduces death or neurodisability at 18-22 months after neonatal encephalopathy, in LMICs. METHODS: We will randomly allocate 408 term or near-term babies (aged ≤ 6 h) with moderate or severe neonatal encephalopathy admitted to public sector neonatal units in LMIC countries (India, Bangladesh or Sri Lanka), to either usual care alone or whole-body cooling with usual care. Babies allocated to the cooling arm will have core body temperature maintained at 33.5 °C using a servo-controlled cooling device for 72 h, followed by re-warming at 0.5 °C per hour. All babies will have detailed infection screening at the time of recruitment and 3 Telsa cerebral magnetic resonance imaging and spectroscopy at 1-2 weeks after birth. Our primary endpoint is death or moderate or severe disability at the age of 18 months. DISCUSSION: Upon completion, HELIX will be the largest cooling trial in neonatal encephalopathy and will provide a definitive answer regarding the safety and efficacy of cooling therapy for neonatal encephalopathy in LMICs. The trial will also provide important data about the influence of co-existent perinatal infection on the efficacy of hypothermic neuroprotection. TRIAL REGISTRATION: ClinicalTrials.gov, NCT02387385 . Registered on 27 February 2015.